Effect of onion top leaves extract on the quality of smoked Heterotis niloticus (Cuvier, 1829) - Jega, Ibrahim Shehu; Michael, Philomina; Mohammed Ribah, Ibrahim (Research in Agriculture Livestock and Fisheries, 2018)
Food preservation techniques to improve the oxidative stability of fish-based foods are gaining renewed research interest in natural compounds of vegetable origin as valid alternatives to synthetic preservatives. This study was designed to determine the effect of Onion Top Leaves Extract (OTLE) on the chemical and sensory qualities of smoked Heterotis niloticus using four concentrations (0, 0.25, 0.5 and 0.75% w/w) and three storage periods replicated four times in a Completely Randomized Design (CRD). A total of 48 fresh samples of H. niloticus were treated with the different concentrations of OTLE, sundried for three hours and smoked using a modified portable drum kiln designed in the laboratory. The treated smoked samples were packaged in paper envelopes and stored at room temperature for a period of three weeks. The results indicated that OTLE concentration had significantly affected (P<0.05) moisture content, crude protein, crude fibre, nitrogen and total volatile base – nitrogen (TVB-N). The storage period was significantly affected (P<0.05) by OTLE for all tested chemical parameters except carbohydrates, (P>0.05). The results for sensory qualities indicated that after three weeks of storage, OTLE exerted a significant effect (P<0.05) on all sensory qualities tested in the study except general acceptability. The results for merit analysis showed that the samples treated with OTLE concentration of 0.25% ranked better followed by 0.5% while 0.75% recorded the lowest performance. For better optimisation of shelf life, chemical and sensory qualities of smoked H. niloticus, the product can be preserved in 0.25% w/w OTLE and stored for one week at room temperature in paper envelopes. Res. Agric., Livest. Fish.5(2): 241-248, August 2018